Ação de substâncias cianogênicas e do campo magnético na redução de tumores: uma revisão integrativa de leitura - Jabrayan, Thais da Cruz Penha (2021)
Cancer treatment has been constantly improved to have the least possible harm to the patient. New therapies are being researched, many of them having as the object of scientific-academic and pharmacological investigation the use of cyanogenic plants and their antitumor chemical compounds that can bring benefits to human health, having the potential to be associated with the magnetic field and thus achieve a benefit better and with reduced adverse effects in cancer treatment. This study aimed to review the effect of cyanogenic substances and the magnetic field on tumor evolution in the literature. The integrative literature review was in the EMBASE, PUBMED, LILACS, BVS, SCOPUS, and MEDLINE databases. A final sample of 14 scientific articles, published from 2011 to 2020, was obtained, highlighting that cyanogenic substances and the magnetic field can help reduce tumors. The most common studies were on the magnetic field, and their research was mainly carried out in vitro, with the frequency of 50Hz that stood out over other frequencies. Among the cyanogenic substances, the most prevalent was amygdalin, with the most used dosage of 10mg/ml. It was possible to conclude that both the magnetic field and cyanogenic substances can reduce tumors